KETERPADUAN EVALUASI DIRI MADRASAH DAN PERENCANAAN PEMBIAYAAN UNTUK MENCAPAI MUTU PENDIDIKAN YANG BERKELANJUTAN - Anita, Anita (LPPM Sekolah Tinggi Ilmu Tarbiyah Al Marhalah Al Ulya Bekasi, Indonesia, 2025)
This study aims to analyze the integration between self-evaluation of Islamic schools (madrasahs) and financial planning in achieving sustainable education quality. A qualitative approach with a case study method was employed to explore practices, challenges, and the impact of such integration. The research was conducted in five madrasahs in South Lampung, representing accreditation categories A, B, and C. Data were collected through in-depth interviews, direct observation, and document analysis, including self-evaluation reports and the Madrasah Budget Plan (RABM). The findings indicate that madrasahs with A accreditation demonstrate more structured self-evaluation practices and effectively integrate the results into financial planning. Conversely, madrasahs with B and C accreditation face challenges such as limited human resources and technology. The study confirms that the integration of self-evaluation and financial planning contributes to education quality improvement, particularly in teacher competency development, infrastructure enhancement, and financial management transparency. This study recommends technical training for Internal Quality Assurance Teams (TPMI) and increased use of technology to support this integration. With an integrated model, madrasahs can more effectively achieve sustainable education quality.